Mc Gill Pain Questionnaire: A Cross-Cultural Adaptation Study in Chronic Neck Pain (International Journal of Physiotherapy, 2023)
Introduction: Due to its complex nature, identification, and treatment of both physical and psychological risk factors is essential in patients with neck pain. Multidimensional pain assessment is an essential prerequisite to planning a multi-modal treatment. McGill Pain Questionnaire is a valid and reliable tool that can assist in multidimensional pain assessment. Hence, this study's objective was to determine the clinimetric properties and usability of the Hindi version of the McGill Pain Questionnaire in patients with neck pain.Methods: After securing permission from the University Ethics board, a cross-culturally adapted Hindi version of the Long Form McGill Pain Questionnaire was administered to evaluate clinimetric properties (validity and reliability) in fifty patients with chronic neck pain.Results: Hindi version of Long Form McGill Pain Questionnaires demonstrated high levels of internal consistency (Cronbach alpha range 0.76- 0.83) and reliability (intraclass correlation coefficient range 0.74-0.85) in patients with chronic neck pain. The Hindi version of LF-MPQ demonstrated adequate construct and concurrent validity when tested with VAS (Pearson r- 0.80) and NDI (Pearson r- 0.79), respectively.Conclusion: The Hindi version of the LF-MPQ was a reproducible and valid tool in chronic neck pain assessment.